The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10144-015-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale spatial and temporal variation in the demographic processes underlying the large‐scale decline of eiders in the Baltic Sea

Abstract: The application of uniform conservation schemes often fails to account for small-scale spatial variation in the drivers of population decline. Demographic comparisons of imperilled populations across locations are therefore crucial for successful conservation, but progress is hampered by lack of long-term data from more than a single population. The recent large-scale decline of eider ducks (Somateria mollissima) in the Baltic Sea is ideal for determining to what extent mechanisms underlying population decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…; Öst et al. ). Incorrect conclusions about monitored populations can arise from short time series (Krebs ; White ); inconsistent methods (Hayward et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Öst et al. ). Incorrect conclusions about monitored populations can arise from short time series (Krebs ; White ); inconsistent methods (Hayward et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, this estimate did not consider population age structure or the fact that individuals across different ages contribute disproportionally to population dynamics. For example, in their study on the decline of female eiders in the Baltic Sea area, Öst et al [ 19 ] showed that the population growth rate of females is far more sensitive to small proportional changes in the mortality of older, experienced breeders than to those of younger age classes. Such a pattern is typical for long-lived vertebrates, including many birds [ 12 , 20 ] and is due to the greater reproductive value of older, reproductive individuals that have high survival [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Öst et al. () found that common eiders breeding along the eastern edge of their range had significantly lower reproductive success than a population breeding in the core of their range. Low fertility may also be the result of negative impacts on survival immature birds once they leave the breeding grounds (birds younger than 1 yr old).…”
Section: Discussionmentioning
confidence: 99%